2016
DOI: 10.4103/0973-6247.187937
|View full text |Cite
|
Sign up to set email alerts
|

Attitude toward blood donation among medical and nonmedical students across Karachi

Abstract: Aim:To evaluate the factors that motivate and discourage medical and nonmedical students from donating blood voluntarily and to assess the level of awareness and knowledge regarding blood donation.Materials and Methods:We conducted a cross-sectional descriptive study from August 2011 to May 2012 across different universities of Karachi covering both private and public sector. Predesigned questionnaires were filled by students. A total of 690 students participated in the study, 345 from each. Data collected was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 13 publications
2
24
2
Order By: Relevance
“…In our setting, the proportion of who had ever donated blood is lower than the one reported in other similar settings where the proportion of blood donors among undergraduate students varied between 18% and 41% [19,[21][22][23][24]26,27]. Such a finding highlights the need of planning strategies in order to motivate undergraduate students in our setting towards blood donation.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…In our setting, the proportion of who had ever donated blood is lower than the one reported in other similar settings where the proportion of blood donors among undergraduate students varied between 18% and 41% [19,[21][22][23][24]26,27]. Such a finding highlights the need of planning strategies in order to motivate undergraduate students in our setting towards blood donation.…”
Section: Discussioncontrasting
confidence: 54%
“…Data collection tool (DCT) was a self-administered questionnaire designed by the authors and based on a review of the literature about blood donation [15,22,25,[27][28][29]. All students who participated and answered to the questionnaire were informed in advance that their contribution would be voluntary and that all information obtained would be used for the only objective of the research.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study suggests that lessons about blood donation should be incorporated in the initial stages of higher education and periodic awareness program should be there for recruitment and retention of donors. This is in contrast to reports by Anwer et al [23] and Hosain et al [22], in which they discussed that greater knowledge does not lead to blood donation. Bani and Giussani [28] reported that higher rate of deferrals in women are responsible for low proportion of female donors.…”
Section: Resultscontrasting
confidence: 56%
“…). A second study conducted on students reported that non‐medical students had given blood more frequently than medical students (27 vs 18%) (Anwer et al, ). A third Pakistani study showed that 90% of high school students considered saving lives as important, but lack of knowledge and a range of fears deterred them from donating blood (Thaver et al, ).…”
Section: Resultsmentioning
confidence: 99%